Do campo projetado ao campo vivido: as trajetórias sociais no espaço rural de Brasil e Espanha - Haas, Jaqueline Mallmann (2012)
This thesis has central theme the social trajectories families established in spaces characterized by external interventions, aiming to understand how the social trajectories families linked to these spaces are transformed and influenced as well as they affect the agent s responses to intervention process that are submitted. The theoretical framework used to assist in that understanding is based on the notions of habitus, field, metropolis and proposed practice by the french sociologist Pierre Bourdieu. From this reference it is possible an interpretation of the differences that are established in apparently homogeneous spaces and also the comprehension of singularities evidenced when totally different contexts. The methodological choice made for this investigation is the Case Study, using different sources and with the lócus of analysis the agrarian reform settlement Lagoa do Junco , situated in the city of Tapes , state of Rio Grande do Sul , and the spanish city Isla Mayor , situated in the Comunidade Autônoma de Andaluzia . Both contexts marked by different production of rice (organic and integrated). Understanding the social trajectories of the families studied passed initially by studying the structure of social spaces where the same are participants, including a historical survey of these. As a result, it appears that the spaces under study are complex and multi-dimensional, having a diverse set of agents acting on the same social trajectories, in this sense both from established families in the Lagoa do Junco , settlement as the city of Isla Mayor , are formed from external interventions, which in turn end determining some forms of action, and the adoption of certain strategies in relation to ways of life. However, those from Pierre Bourdieu, the social trajectories of families also show strongly influenced from a previous habitus, and from the field they are inserted. The clash between external intervention and individual questions also revealed the final restrictions on freedom of the families of both latitudes. Leading to the field projected to the field actually lived by agents, there are permeated social trajectories by process of intervention, that cause the projected and lived in rural Brazil and Spain are very disparate.